Cultural psychology for a new era of citizenship politics. (June 2019) - Ellis, Basia D; Bhatia, Sunil
In the current era of citizenship politics, both legal citizenship and cultural citizenship have become highly contested social categories and new bases for social discrimination. Psychological studies of migration thus need to consider more explicitly how shifting sociopolitical contexts shape migrant life opportunities and how migrants respond to their shifting circumstances. Cultural psychologists have much to contribute to this project given their focus on the ways cultural experiences are shaped at once by broader social determinants and the intentional acts of social agents who navigate diversely organized worlds. However, we argue that cultural psychologists need to integrate critical concepts into cultural psychological studies of migration to avoid both overlooking important determinants of migrant lives and inadvertently perpetuating social inequalities and discriminatory policies. Drawing upon qualitative research conducted with Polish "irregular" migrants in Canada and Sikh Americans, we show how critical concepts such as "illegalization, " "deportability, " and "cultural citizenship" can help expand cultural psychological inquiry to better understand contemporary immigrant experiences. We conclude with discipline-specific recommendations for building a cultural psychology fit for the study of migration in the 21st-century.